Effects of Soil Organic Matter Properties and Microbial Community Composition on Enzyme Activities in Cryoturbated Arctic Soils - Jörg Schnecker (University of Vienna); Birgit Wild (University of Vienna); Florian Hofhansl (University of Vienna); Ricardo J. Eloy Alves (Department of Ecogenomics and Systems Biology, Faculty of Life Sciences, University of Vienna); Jiří Bárta (Department of Ecosystems Biology, University of South Bohemia); Petr Čapek (Department of Ecosystems Biology, University of South Bohemia); Lucia Fuchslueger (University of Vienna); Norman Gentsch (Institut für Bodenkunde, Leibniz Universität Hannover); Antje Gittel (Austrian Polar Research Institute); Georg Guggenberger (Institut für Bodenkunde, Leibniz Universität Hannover); Angelika Hofer (University of Vienna); Sandra Kienzl (University of Vienna); et al. (PLoS ONE, 2014)
The abstract is available here: https://uscholar.univie.ac.at/o:471694 The abstract is available here: https://uscholar.univie.ac.at/o:471694